CPR Induced Consciousness During Out-of-Hospital Cardiac Arrest: A Case Report on an Emerging Phenomenon. (4th March 2017) - Pound, Joshua; Verbeek, P. Richard; Cheskes, Sheldon
ABSTRACT: Background : High quality cardiopulmonary resuscitation (CPR) has produced a relatively new phenomenon of consciousness in patients with vital signs absent. Further research is necessary to produce a viable treatment strategy during and post resuscitation.Objective : To provide a case study done by paramedics in the field illustrating the need for sedation in a patient whose presentation was consistent with CPR induced consciousness. Resuscitative challenges are provided as well as potential future treatment options to minimize harm to both patients and prehospital providers.Case Report : A 52-year-old male presented as a witnessed out-of-hospital cardiac arrest (OHCA). During CPR the patient began to exhibit signs of life including severe agitation and thrashing of his limbs while CPR was ongoing for ventricular fibrillation prior to defibrillation. Resuscitation became considerably more complicated due to the violent and counterintuitive motions done by the patient during their own resuscitation. Despite the atypical presentation of cardiac arrest the patient was successfully resuscitated employing high quality CPR, standard advanced life support (ALS) care as well as two double sequential external defibrillation shocks. The patient underwent emergency percutaneous coronary intervention (PCI) for a 100% occlusion of his left anterior descending artery (LAD). The patient returned home 3 days later fully recovered with a Cerebral Performance Score of 1.Conclusion : CPR induced consciousness is emerging as a new phenomenon challenging providers of high quality CPR during cardiac arrest resuscitation. Our case report describes the manifestations of CPR induced consciousness as well as the resuscitative challenges which occur during resuscitation. Further research is required to determine the true frequency of this condition as well as treatment algorithms that would allow for appropriate and safe management for both the patient and EMS providers.